Endometrial Cytology with Tissue Correlations - Maksem, John A.; Robboy, Stanley J.; Bishop, John W.; Meiers, Isabelle (Essentials in Cytopathology, 2009)
As compared with cytology's use in other organ systems, direct cytological examination of the endometrium is not a widely practiced diagnostic procedure. This volume highlights endometrial cytology as an effective method for ensuring endometrial normalcy and discovering and diagnosing malignant and premalignant states. Endometrial Cytology with Tissue Correlations covers the background, collection technique, diagnostic criteria and pitfalls, as well as reliability of endometrial cytology. This volume, part of the Essentials in Cytopathology book series, fits into the lab coat pocket and is ideal for portability and quick reference. Each volume in the series is heavily illustrated with a full color art program, while the text follows a user-friendly outline format. John A. Maksem, M.D., is Director of Cytopathology, Orlando Health, Orlando, Florida. Stanley J. Robboy, M.D., is Head of Gynecologic & Obstetrical Pathology, Department of Pathology, Duke University Medical Center, Durham, North Carolina. John W. Bishop, M.D., is HS Clinical Professor of Pathology, University of California, Davis, Sacramento, California. Isabelle Meiers, M.D., is Head of Cytology at University Hospital Lewisham, London, United Kingdom. .